Delay in seeking care for breast symptoms and its associated factors - Yen, Soh Jien (2021)
Background: Breast cancer is the most common cancer among Malaysian and in women worldwide. The incidence of breast cancer is increasing yearly. Early presentation and thus, early detection of breast cancer will lead to better prognosis and survival. Objective: This study aimed to investigate the delay of presentation time in women with breast symptom and its associated factors. Methods: The study was conducted between January to October 2020, recruiting women with new breast symptoms at their first visit to the clinic. Face-to-face interviews using the standardised Malay language questionnaires, and the date of symptom first develop and first visit the clinic was recorded. Presentation time was calculated based on the number of days between the two date. Those with presentation time more than 90 days was considered as a delayed group. Associated factors were recorded, cross-tabulation and multiple logistic regression with the delay presentation for were used for analysis. Result: In total, 106 respondents were included. The mean age of the respondents was 33.99 (SD 11.207), and most of them (73.6%), were age 39 and younger. The respondents mainly were Malay ethnicity (98.1%) and Chinese (1.9%). Most of the respondents first visited the local government health clinic (35.8%) for breast symptoms. They presented symptoms were breast lump (75.5%), followed by pain (15.1%), nipple discharge (5.7%), skin changes of breast (0.9%) and others (2.8%). Only 10.4% of the respondents went for alternative treatment before for the breast symptoms. The mean of presentation time was 98.91 days (SD 323.71) with median of 14.5 days. Approximately 61.3% of the respondents came within 1-month time. Only 19.8% of the respondents had delay presentation of more than 3 months. The factor that significantly associated with the delay in the presentation was the interpretation of the symptom as not dangerous with adjusted OR 3.05 (95% CI 1.11,8.38) with adjustment of the symptom of breast lump Conclusion: The percentage of delay presentation was lower compared to the previous local study in Malaysia. The significant factor associated with the delay for breast care was the interpretation of the symptom as harmless. The future education program must be targeted and tailored to the local community.